(untitled) (LACCEI, 2024)
The general objective of this research was to determine water quality through physicochemical and sediment analysis. Also, to evaluate the benthic macroinvertebrate community through biotic indices (EPT, BMWP/Bol, BMWP/Col, ABI and CERA) in the Perlamayo and Tacamache rivers. Seven monitoring points were established according to the degree of intervention by anthropogenic activity. During the months of February (rainy season) and July (dry season), the results of the physicochemical variables were compared to Peruvian Environmental Quality Standards. According to Supreme Decree No. 004-20017-MIMAN, and Sediments compared to the Canadian ECA TEL (Threshold Effect Level). To study the relationship between macroinvertebrate communities and environmental variables. An statistical analysis was carried out to determine which pressures most affect the benthic community, using a simple regression model. The results obtained show that the distribution and composition of the benthic community is determined by the physicochemical parameters of temperature, pH, conductivity, dissolved oxygen and the concentrations of heavy metals. Six orders and 16 families of benthic macroinvertebrates were identified. Including, Leptophlebiidae, Gripopterygidae, Leptoceridae, Hydrobiosidae, Hyalellidae and Chironomidae the ETP index gave a poor water quality the BMWP/Bol and BMWP/Col indices gave a critical quality the ABI and CERA indices showed a moderate quality. In conclusion, the levels of alteration evaluated in this research are a useful tool for determining the ecological quality of the Perlamayo and Tacamache river systems. Proving to be an appropriate method for the evaluation and monitoring of other watersheds in the Cajamarca region, Peru.